Sinergi Mahasiswa dan Industri dalam Peningkatan Kompetensi dan Penerapan Teknik Pengecoran Logam di CV Bengkel Bukit Harapan - Iswandi, Iswandi; Darianto, Darianto; Hermanto, Tino; Aldhori, Yopan Rahmad; Supriatno, Supriatno; Haniza, Haniza (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2025)
Community Service Activities by the Mechanical Engineering Study Program of Medan Area University aim to bridge the world of higher education with the needs of local industry. This activity takes the form of industrial visits and hands-on learning at CV Bengkel Bukit Harapan, a metal casting manufacturing workshop located in Deli Serdang, North Sumatra. The methods used include theoretical counseling, field observation, open discussions, and direct practice. Students gain real-world experience in the metal casting process, from melting and pouring to work safety aspects and product finishing. The interaction between lecturers, students, and industry partners results in a two-way exchange of Knowledge that enriches students' technical insights and practical skills while also providing industry partners with valuable technical input. This activity demonstrates that a field-based collaborative approach enhances the effectiveness of learning and fosters stronger campus-industry partnerships. The results of this activity will serve as a model for sustainable synergy in community empowerment through technical education.